PENGEMBANGAN PERMAINAN SIRKUIT MITIGASI BENCANA GEMPA BUMI UNTUK MENINGKATKAN SELF AWARENESS ANAK USIA DINI - Ningtyas, Dhita Paranita; Risina, Duana Fera (Jurnal Caksana : Pendidikan Anak Usia Dini, 2018)
ABSTRACTEarthquakes are vibrations or shocks that occur on the surface of the earth. Earthquakes are caused by the movement of the earth's plates. Most earthquakes are caused by the release of energy produced by the pressure made by moving plates. The longer the pressure gets bigger and finally reaches a state where the pressure cannot be restrained. This study aims to find earthquake disaster mitigation game models using circuit games made with natural materials to increase children's self awareness. The research approach uses modified Research and Development (R and D) in three research steps, namely: Preliminary research, model development and model validation tests. The preliminary study contains a literature study for the theme of disaster mitigation learning and study planning document B TK learning at BKB Mawar. Model development has three steps developed from three concepts, namely identification of themes into sub-themes, analysis of themes into activities and planning unit themes. The model validation test is expert validation. The result is significant, effective and feasible. The finding of this study is the creation of an earthquake disaster mitigation circuit game, this mitigation circuit game is a game used to help children understand how the earthquake disaster responds. This game can be given to those in Indonesia and can be applied in all regions that have the same geographical situation, which aims to improve children's self-awareness of disasters.Keywords: Games, Mitigation Circuits, Earthquakes, Self Awareness, Early Childhood